In Vitro Micropropagation of Eria Lasiopetala (Willd.) Ormerod- A Native Medicinal Orchid in Bangladesh (Journal of Bio-Science, 2024)
The present study focuses on the asymbiotic germination of seeds through in vitro culture of Eria lasiopetala, a native medicinal orchid in Bangladesh.  Out of the four basal media, MS was found to be the most effective medium, where 93.58±0.374% seed germinations were recorded. Different plant growth regulators (PGRs), e.g. BAP, Kin, NAA and were used for secondary protocorm proliferation, plantlet development, and multiplication of shoot buds through in vitro conditions. The maximum number of secondary protocorms (12.80±0.115) were developed that were derived from primary protocorms on MS medium fortified with 0.5 mg/l BAP and 1.0 mg/l NAA. Data revealed that 0.5 mg/l BAP + 0.25 mg/l NAA showed the best combination for height elongation of plantlets (3.12±0.012 cm) in MS medium. While for multiple shoot buds (MSBs) 1.0 mg/l BAP + 0.5 mg/l NAA showed better (6.8±0.127) performance than other combinations of PGRs. The single shoots were isolated from the multiple shoots and sub-cultured on ½MS medium supplemented with NAA (0.5 - 2.0 mg/l), IAA (0.5 - 2.0 mg/l) and IBA (0.5 - 2.0 mg/l) for root induction. The maximum number of roots (7.53±0.176) and its growth (4.61±0.01 cm) were found in ½MS medium supplemented with 1.0 mg/l IAA. The well rooted plantlets were hardened and successfully transferred after acclimatization in pots containing the mixture of coconut husk, charcoal and brick pieces in the ratio of 2:1:1 and eventually established under natural condition.J. Bio-Sci. 32(1): 45-60, 2024